2014
DOI: 10.1371/journal.pgen.1004372
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Functional Annotation of SIX6 Variants in Primary Open-Angle Glaucoma

Abstract: Glaucoma is a leading cause of blindness worldwide. Primary open-angle glaucoma (POAG) is the most common subtype and is a complex trait with multigenic inheritance. Genome-wide association studies have previously identified a significant association between POAG and the SIX6 locus (rs10483727, odds ratio (OR) = 1.32, p = 3.87×10−11). SIX6 plays a role in ocular development and has been associated with the morphology of the optic nerve. We sequenced the SIX6 coding and regulatory regions in 262 POAG cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 32 publications
8
78
1
1
Order By: Relevance
“…Our findings, along with prior studies, 43, 44 support the importance of SIX1-SIX6 in quantitative trait measures such as RNFL. Future studies to understand the genetic contribution of these additional markers identified in the SIX1-SIX6 region, either individually or in combination, on RNFL thickness would be interesting and meaningful.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings, along with prior studies, 43, 44 support the importance of SIX1-SIX6 in quantitative trait measures such as RNFL. Future studies to understand the genetic contribution of these additional markers identified in the SIX1-SIX6 region, either individually or in combination, on RNFL thickness would be interesting and meaningful.…”
Section: Discussionsupporting
confidence: 88%
“…43, 44 Ulmer et al, 43 examining the sequence variants of the coding and regulatory regions of SIX6 in POAG , identified 6 non-synonymous SNPs, of which only 1 SNP (rs33912345) was a common variant. This SNP is in high linkage disequilibrium with our lead SNP of rs10483727 (r 2 = 1.00; D′ = 1.00 using SNAP 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the specificity of our in vivo model we also tested for genetic interaction between GDAP1 , a bona fide CMT driver, and 3 genes that have not been associated previously with peripheral neuropathy. Two of those are expressed in the CNS and cause other neuropathologies ( SIX6 : optic nerve atrophy [Carnes et al, 2014]; RP1L1 : retinal degeneration and cerebellar disorganization [Davidson et al, 2013]), and the third is expressed ubiquitously and causes VACTERL ( ANKRD6 ; unpublished data). We injected sub-effective doses of each of the tested genes alone and also in pair-wise combinations (Supplementary Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…To date, genetic studies on cpRNFLT have shown consistent contributions of the single nucleotide polymorphisms (SNPs) rs33912345 and rs10483727 located within the SIX1/SIX6 loci to cpRNFL thinning in the superior and inferior sectors, but not in the temporal, nasal, and global sectors 3032 . The significance of the SIX1/SIX6 locus in glaucoma was initially discovered by GWAS for VCDR and primary open-angle glaucoma (POAG), and subsequent studies confirmed the association of polymorphisms in this region with glaucoma onset.…”
Section: Introductionmentioning
confidence: 99%